The basics of transferring risks in international trade contracts - خندان شذى عبد الجبار; حسين أكرم محمد (Journal of Legal Sciences, 2021)
The goods sold during the transport phase may be exposed to the risk of the buyer’s state, whether those risks are land, sea or air, resulting in the loss of the goods in whole or in part, or damage, as if they were destroyed by the ship sinking or colliding with another or the cause of the loss or damage is due to a fire, as in the case of a spark on the goods, and the goods is a combustible material. The risk should be borne by one of the parties. To identify the responsible party for the risks, it should determine a particular moment for transferring risks. There has been a difference in legislation, whether at the national or international level, on determining the basis for risk transfer.